Mulheres negras nas comarcas sergipanas (1888-1940) : gênero, “raça” e classe - Santos, Selma da Silva (2018)
In Sergipe, when the birth of the republic and its process impacted social relations, the economic scenario previously centered on slave labor turned to wage labor, also due to the decadence of the Sergipe sugar cane culture, together with the end of the slave system. Sugar as the flagship of the Sergipe economy impacted on inner cities such as Laranjeiras and Maruim, which together with Aracaju stood out in the economic, political and cultural scenario. In the midst of these transformations the population also changed its daily life, the city was modernized, urbanization of streets, industries became more present in the state, especially the textile factories, which impacted the way of life of people who saw in these changes opportunities a better life in other cities. The migration of people between cities reflected in demographic censuses showing continued population growth. The women were absorbed by the factories, who in search of cheap labor saw in these subjects a very profitable productive force, and in domestic work, however, they were low-paid and unqualified jobs. Women entered public spaces and places previously occupied mostly by men. It is in this scenario of changes that the present research intends to reveal the life of the black and poor women of the sergipan comarcas. From the criminal processes of the cases of defloramento, we present the daily life of these women in the moment that they activated the justice to defend their honor or of a familiar entity. The crimes as a historical source provide us with information for this work, delimited within the time frame from 1888 to the 1940s, occurring in the cities of Laranjeiras, Maruim and Aracaju, municipalities and capital of Sergipe respectively. From a descriptive and analytical approach, the data were collected specially in the testimonies and in the body of crime, analyzed qualitatively and quantitatively and with the use of tables, in order to draw a profile of the social subjects of this study. The present research also seeks to corroborate with the field of social history raising evidence of the autonomy of black women and their ways of life, even the society imposing a subalternized and objective social role, making their protagonism invisible.